Comparison and Evaluation of the Molecular Typing Methods for Toxigenic Vibrio cholerae in Southwest China - Liao, Feng; Mo, Zhishuo; Chen, Meiling; Pang, Bo; Fu, Xiaoqing; Xu, Wen; Jing, Huaiqi; Kan, Biao; Gu, Wenpeng (Frontiers in Microbiology, 2018)
Vibrio cholerae O1 strains taken from the repository of Yunnan province, southwest China, were abundant and special. We selected 70 typical toxigenic V. cholerae (69 O1 and one O139 serogroup strains) isolated from Yunnan province, performed the pulsed field gel electrophoresis (PFGE), multilocus sequence typing (MLST) and multilocus sequence typing of virulence gene (V-MLST) methods, and evaluated the resolution abilities for typing methods. The ctxB subunit sequence analysis for all strains have shown that cholera between 1986 and 1995 was associated with mixed infections with El Tor and El Tor variants, while infections after 1996 were all caused by El Tor variant strains. Seventy V. cholerae obtained 50 PFGE patterns, with a high resolution. The strains could be divided into three groups with predominance of strains isolated during 1980s; 1990s and 2000s respectively, showing a good consistency with the epidemiological investigation. We also evaluated two multilocus sequence typing method for V. cholerae, one was used 7 housekeeping genes (adk, gyrB, metE, pntA, mdh, purM and pyrC), and all the isolates belonged to ST69; another was used 9 housekeeping genes (cat, chi, dnaE, gyrB, lap, pgm, recA, rstA and gmd). A total of 7 sequence types were found by using this method for all the strains; among them, rstA gene had 5 alleles, recA and gmd have two alleles, and others had only one allele. The virulence gene sequence typing method (ctxAB, tcpA and toxR) showed that 70 strains were divided into 9 ST types; among them, tcpA gene had 6 alleles, toxR had 5 alleles, while ctxAB was identical for all the strains. The latter two sequences based typing methods also had consistency with epidemiology of the strains. PFGE had a higher resolution ability compared with the sequence based typing method, and MLST used 7 housekeeping genes showed the lower resolution power than 9 housekeeping genes and virulence genes methods. These two sequence typing methods could distinguish some epidemiological special strains in local area.